The role of angiotensin-converting enzyme 2 in COVID-19 induced lung injury - Torabi, Sara; Bahreini, Farbod; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2020)
The novel coronavirus disease (COVID-19) has affected people around the world both physically and psychologically. As result, developing coronavirus-specific vaccine and/or therapeutics is now a top priority for public health agencies. Since our findings about COVID-19 are relatively new, the current knowledge about the molecular mechanism involved in pathogenicity and virulence of the novel coronavirus is not advanced. Understanding angiotensin-converting enzyme 2 (ACE2), the receptor for the coronavirus, is significantly important. To better illustrate the role of ACE2 in the severity of COVID-19 and the impact of currently used drugs on this receptor, this paper briefly reviews newly published articles in this regard.